Factors Affecting Life Satisfaction Among People With Physical Disabilities During COVID-19: Observational Evidence From a Korean Cohort Study - Myoungsuk Kim; Seung Hee Ho; Hayeon Kim; Jaemin Park (Annals of Rehabilitation Medicine)
Objective To determine the factors influencing the life satisfaction of people with physical disabilities during the COVID-19 pandemic, considering demographics, disability-related characteristics, health behaviors, and psychosocial characteristics. Methods We used cross-sectional data from 301 respondents of the 2021/2022 survey of the Korean Health Cohort Study for People with Physical Disabilities. Descriptive statistics were used to analyze the research subjects’ characteristics, and chi-square tests and multiple logistic regression were used to identify the determinants of life satisfaction. Results Among socio demographic variables, occupation had a strong association with life satisfaction. Significant health behavior variables included daily regular meals, weight control effort, and chronic pain. All psychosocial characteristics (perceived stress, depression, suicidal ideation, cognitive function assessment, subjective health status, family satisfaction, income satisfaction) were strongly associated with life satisfaction. Results of the analysis of factors affecting life satisfaction showed that unemployment, lack of regular exercise, elevated stress, suicidal thoughts, and dissatisfaction with family contributed to increased life dissatisfaction. Conclusion Economic support through job creation that considers the specific characteristics of people with disabilities, and social access through community integration services that encourage participation in social activities, should be prioritized.